PTU-015 Natural history of varices in the era of non-invasive assessment. Issue 2 (June 2019) - Johnston, Michael Patrick; Wright, Mark
Abstract : Introduction: Guidelines recommend endoscopic variceal screening and surveillance in patients with cirrhosis. 1 The rate of development of large oesophageal varices needing treatment appears to be 7–8% per year. 2, 3 However, with a growing proportion of diagnoses also now being made by Fibroscan we hypothesize that this rate may be lower. Methods: We performed a case note review of 304 patients with a liver stiffness measurement (LSM) more than 15 kPa on Fibroscan between April 2012 and February 2016. Patients also had to have an endoscopy within 6 months to be included. We excluded patients with previous decompensation, hepatocellular carcinoma, inaccurate LSM (IQR >30%) or LSM felt to be aberrant by the clinician based on clinical, radiological or histological grounds. For patients with hepatitis C (HCV) we used post-SVR LSM. We recorded sex, age, aetiology of liver disease, LSM, platelet count, endoscopic findings at 0–6 months and at 24–48 months, duration of follow-up, incidence of bleeding or death. Varices were documented as absent, small or large. Results: 113 patients were included. The most common aetiologies were non-alcoholic fatty liver disease (36.2%), alcoholic liver disease (29.3%) and HCV (20.7%). Mean age was 59.3 ± 11.5 years. LSM was 33.4 ± 17.1 kPa. Median follow-up was 4 years. Baseline endoscopy revealed no varices in 76 patients (67.3%), small varices in 29 patients (25.7%) and large varices in 8 patients (7.1%). 6 of the patients (5.3%) had a variceal bleed within 12 months. All large varices underwent band ligation (VBL) as per local practice. 58 patients went on to have a repeat endoscopy at 24–48 months. There was no progression of absent/small varices in 50 patients (86.2%) and a static gastric varix in 1 patient (1.7%). There was progression to large varices in 7 patients (13.8%) including 1 variceal haemorrhage. Conclusions: In our group of patients with compensated cirrhosis the rate of development of clinically significant varices over 3 years appears to be lower than previous estimates. Weaknesses of the study include its retrospective nature and drop out rate. However, the findings would fit with our perception of an increased rate of diagnosis of advanced chronic liver disease by Fibroscan. The natural history of varices may be different to historic populations diagnosed on histological grounds or overt clinical and radiological features. References: U.K. Guidelines on the Management of Variceal Haemorrhage in Cirrhotic Patients, Gut ( 2015) 64(11) 1680–1704 R Groszmann, G Garcia-Tsao, J Boschet al, Beta-blockers to prevent gastroesophageal varices in patients with cirrhosis, NEJM ( 2005) 353(21) 2254–2261 M Merli, G Nicolini, S Angeloniet al, Incidence and natural history of small esophageal varices in cirrhotic patients, J Hepatol . ( 2003) 38(3) 266–272